The importance of "collectivity" for transformative pastoral food systems - Flintan, Fiona E.; Shukuku, Kelvin M. (2023)
Presentation on the importance of collectivity in using, managing and governing resources in pastoral systems and their resilience. Research based on a household survey conducted in Ethiopia in 2018 and presented at Tropentag 2023.